EFFECT OF THE RADIATION OF GAMMA RAYS ON CASPASE-3 EXPRESSION IN RATTUS NORVEGICUS WISTAR MALE VARIANT BRAIN CELL WITH IMMUNOHISTOCHEMISTRY METHOD - Alam, Ahmad Bayhaqi Nasir; Rahayu, Masruroh; Islani, Ahmad Zaki Sukma (Malang Neurology Journal, 2015)
Â Background. The brain is an organ that has an important function potentially exposed to bad influences of radiation, especially on the head neck tumors. Gamma rays interact with body molecules causing damage to DNA and subsequently apoptosis. Caspase-3 plays an important role in apoptosis as effector caspase. Objective. To prove that the radiation of cobalt-60 gamma rays in Rattus norvegicus Wistar male variant causes brain cell apoptosis by the number of apoptotic cells more than in the single-dose fractionation. Methods. This Experimental research using animals were randomly divided into 3 groups: control, single and fractionation.Results. An increase in apoptotic index in the irradiated brain cells in single dose and fractionation dose compared by control group were significant (ANOVA, p > 0.05 ). Sequentially, the highest apoptotic index in a single group, fractionation, and control.Conclusion. The provision of radiation Cobalt - 60 gamma rays cause brain cell apoptosis Rattus norvegicus Wistar male variant and a single dose to cause apoptosis of brain cells more than the dose fractionation.